High‐speed high‐voltage solid‐state Marx generator based on SiC MOSFETs. Issue 6 (3rd January 2023) - Dehghan, S. Mohammad; Seviour, Rebecca; Hunt, Steve
Abstract: This paper presents a high‐speed, high‐voltage, solid‐state Marx generator based on silicon carbide MOSFETs. The objective was to develop a high‐rate repetitive, short‐pulse, high‐voltage and efficient generator for medical particle accelerator applications. To achieve this goal, a 720 kV Marx generator forming from 1445 kV stages was designed. Each stage includes several SiC devices in series to reach desired voltage and speed. Compared to the existing Marx generators, the proposed Marx generator is capable of producing shorter pulses with higher voltage. We present the experimental results of a three‐stage prototype Marx generator capable of producing 15 kV at 40 A output with a 200 nS pulse with a repetition rate of 500 Hz. Abstract : A high‐speed, high‐voltage and solid‐state Marx generator is based on silicon carbide MOSFETs. Compared to the existing Marx generators, the proposed Marx Generator is capable of producing shorter pulses with higher voltage. Presenting experimental results of a three‐stage prototype Marx generator capable of producing 15 kV at 40 A output with a 200 nS pulse with a repetition rate of 500 Hz.